Short-term adaptations to traditional and daily undulating knee extensor training in strengthtraining experienced women - Pelzer, T.; Ullrich, B.; Pfeiffer, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Strength training periodization has been successfully applied to various athletic populations over the last decades. Currently, traditional (TP) and daily-undulating (DUP) periodization models are most frequently discussed in literature but the more effective approach is yet to be determined. Conflicting study outcomes were hereby mainly due to methodological limitations such as insufficient control of mechano-biological exercise characteristics in the majority of studies (Toigo & Boutellier, 2006; Harries et al., 2015). For more accurate program comparison, this work analyzed TP and DUP during short-term knee extensor training with biofeedback-controlled training stimuli. METHODS: 19 strength-training experienced women performed 6 weeks of unilateral dynamic knee extensor training with 3 sessions per week, exercising 1 leg using TP and the contralateral leg using DUP. Intensities varied between 40%, 60%, and 80% of individual one repetition maximum (1RM) and were progressively adjusted in a weekly rhythm. To detect possible outcome differences, maximum voluntary isometric and isokinetic-concentric knee extensor strength (MVC), EMG-estimated neural drive of the M. quadriceps femoris (QF), and muscle architecture of the M. vastus lateralis (VL) and M. rectus femoris (RF) were analyzed by 2-factor ANOVA (time * training leg). RESULTS: Significant temporal changes occurred for isometric (TP: 15%, DUP: 13%) and isokinetic-concentric (TP: 8%, DUP: 10%) knee extensor MVC and 1RM (TP: 18%, DUP: 23%). VL and RF-muscle thickness significantly (P<0.05) increased ranging from 12-20% for TP and from 13-19% for DUP respectively. Maximal voluntary QF-EMG-activity remained statistically unchanged in both legs. Importantly, no significant periodization effects occurred for any study outcome and similar effect sizes were calculated in both training legs. DISCUSSION: According to current meta-analysis (Harries et al., 2006), our results indicate that TP and DUP were equally adapted to improve maximum QF knee extensor strength, EMG-estimated neural drive and VL + RF muscle architecture following 6-weeks of biofeedbackcontrolled dynamic strength training. Thus, mechanical alterations in the exercises force-velocity characteristics for instance might act as key neuromuscular adaptation triggers during intensive short-term training periods rather than stimuli periodization.